The Impact of Mesopores on the Mechanical Stability of HKUST‐1: A Multiscale Investigation. Issue 27 (27th July 2016) - Dürholt, Johannes P.; Keupp, Julian; Schmid, and Rochus
Abstract : Correlated missing node defects can lead to mesoporosity in MOFs. In order to investigate the effect of such cavities in the microporous crystalline material, spherical pores of increasing size were cut into HKUST‐1, and the resulting inner surface was completely saturated. Our recently developed coarse‐grained force field was used to relax these systems and to assess the mechanical stability by computing the bulk moduli. In a multiscale fashion, atomistic models were generated systematically from the coarse‐grained relaxed structures in order to determine void fraction, surface area, and the relative mesoporous void volume. Despite the presence of mesopores with large radii of above 20 Å, the lattice parameters shrink only by a negligible amount. The bulk moduli are reduced, but overall a sufficient mechanical stability is found, consistently with experimental observations. Interestingly, for a fixed amount of defect degree, and thus mesoporous void volume, larger cavities lead to higher mechanical stability. For small mesopores in the size range below that of a HKUST‐1 unit cell we observe unexpected trends due to the additional surface area generated by saturating the inner surface of the mesopore. With a large number of small mesopores, this can lead to an effective increase in the gravimetric surface area. Abstract : The impact of mesopores due to defects in HKUST‐1 on surface areas and mechanical stability was investigated by a multiscale simulation approach, combining coarse‐grained and atomistic methods. The mechanical stability is related to size and concentration of the mesopores, and unexpected trends in volumetric and gravimetric surface area are pointed out.